PENGARUH HARGA, KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI KANTIN PT EUDE INDONESIA - Kusmanto Kusmanto; Sri Muryanti (Universitas Sains dan Teknologi Komputer, 2019)
This study aims to analyze how the effect of price, product quality and service on purchasing decisions at PT. Eude Indonesia. The sample in this study was the canteen consumers of PT. EUDE Indonesia by distributing questionnaires to 93 respondents. The technique in this study used simple random sampling. Data were collected using a questionnaire. Data analysis using multiple regression analysis techniques. The results showed that the price and product quality had no and insignificant effect on purchasing decisions, while service had an effect on purchasing decisions.